Contractor Selection Criteria: a Study on Malaysian Public Construction Projects - Rashid, Izwan; Ismail, Syuhaida; Mohamed, Zainai; Latif Saleh, Abd. (International Journal of Engineering and Technology, 2018)
The complexity of a construction project renders the implementation of a systematic approach in selecting contractors to be of vital importance, especially for the public construction projects. Nevertheless, public construction projects in Malaysia often suffer from delay, over budget and low-quality issues. These are very much affected by the contractors who tend to manipulate the tender price with the sole intention of getting the contract, thus led to many issues throughout the projects delivery. Hence, this paper is aimed to investigate a list of contractor selection criteria for public construction projects in Malaysia. A total of 43 selection criteria have been identified and categorised into seven categories from an initial review via content analysis. These findings were then verified via a questionnaire survey, which was responded by 276 local Malaysian construction industry practitioners. Data collected were analysed using the IBM Statistical Package of Social Sciences (SPSS). The analysis showed that all 43 selection criteria were significant in selecting contractors. It is hoped that the findings of this paper would encourage the governing bodies and authorities to consider the use of multi criteria assessment in selecting contractors for public construction projects, rather than being solely reliant on the tendered price.Â